The Trouble with Modeling the Human into the Future Climate. Issue 2 (3rd July 2022) - Harris, Dylan M.
Abstract : Because contemporary climate change is driven by anthropogenic forcings, it is necessary to factor humanity's impact into climate models. Given that not all humans are responsible for current climate change, and that many people are already unequally impacted by climate change, it is necessary to develop a more nuanced understanding of the human in climate modeling. Without this nuance, future climate policy, as determined by climate modeling, will potentially replicate historic inequalities that are already present in attributions to and impacts from a rapidly changing climate. This paper begins by briefly outlining how climate models are built, and the ways they are used in climate politics. Then, borrowing methods from climate modelers, this paper turns towards Sylvia Wynter's work to model the human. The ultimate aim of this paper is to think more expansively and creatively about how genres of humanity can better be represented in climate science and policy with an eye towards more just futures.